Experimental Study on Flight Time and Frame Toughness of Quadcopter Based on Waste Polystyrene Paper - Mastariyanto Perdana; Meiki Eru Putra; Farid Septio Matrilindo (Jurnal Teknik Mesin, 2020)
Application of natural composite materials for aerial fields has been widely developed. One of the uses of natural composite materials for Unmanned Aerial Vehicle (UAV) frame. In this study, waste polystyrene paper, bagasse powder and eggsheel powder was used for material of UAV frame. Type of UAV was made in this study is quadcopter. Addition of volume fraction of waste polystyene paper to 65 % in green composite material. The aims this study was determine the flight time and toughness frame of quadcopter based on waste materials. This study showed that there was increase of quadcopter flight time with the addition of waste polystyrene paper in composites up 65% by volume fraction. Addition of waste polystyrene paper in composites up 65% by volume fraction, the results showed that the toughness frame of quadcopter was decreased. Photomacro was used to show the stucture and porosity of frame quadcopter based on natural composite material.